Recovery - Oriented Care for Older People: Staff Attitudes and Practices - Koder, Deborah (International Journal of Psychosocial Rehabilitation, 2018)
There is a push to change the focus of mental health delivery from symptom reduction to recovery orient- ation where self-determination and choice are central to programmes. Whilst there is a robust literature on recovery definition, assessment and training, this has not been matched with studies of recovery with older adult consumers or staff working in older adult settings. The purpose of this sequential explanatory study was to identify the recovery attitudes and practices of the staff from the Sydney Local Health Dis- trict Specialist Mental Health Service for Older People (SMHSOP), Australia. Fourteen members of staff completed two self-report recovery measures and subsequently took part in focus group interviews. Res- ults of this mixed methods study suggested that whilst mental health staff in this sample supported the self-definition and individuality aspects within the recovery model, risk management remains problemat- ic with this population. Clinical experience mediated the extent of knowledge and practices within a re- covery framework. Barriers to implementing recovery oriented practice included client incapacity and the expectation of consumers. The suitability of current recovery concepts and measures to older populations is discussed.